Glucagon-like Peptide-1 Improves Fatty Liver and Enhances Thermogenesis in Brown Adipose Tissue via Inhibiting BMP4-Related Signaling Pathway in High-Fat-Diet-Induced Obese Mice - Wang, Xingchun (Int J Endocrinol, 2021)
OBJECTIVE: Glucagon-like peptide-1 (GLP-1) receptor agonist is effective in decreasing blood glucose and body weight. It could improve fatty liver with unclear mechanisms. Hence, we aimed to explore whether GLP-1 could improve fatty liver by regulating the BMP4-related signaling pathway. METHODS: Fifteen C57BL/6 mice were randomly assigned to 3 groups. Group A and Group B were fed with a high-fat diet (HFD) to induce fatty liver while Group C was fed with a regular diet (RD) for 24 weeks. Group A and Group B received a subcutaneous injection of exenatide and vehicle (0.9% NaCl), respectively, once daily at doses of 10 nmol/kg during the last 8 weeks. Bodyweight, liver weight, and lipid levels were measured. Histological analyses of liver tissue were performed. The expression of protein and gene measured by western blotting and real-time polymerase chain reaction (RT-PCR) was compared. RESULTS: Eight-week exenatide treatment significantly decreased body weight in Group A (from 44.08 ± 2.89 g to 39.22 ± 1.88 g, P = 0.045). Group A had lower body weight and liver weight than Group B at 24 weeks (39.22 ± 1.88 g vs. 47.34 ± 2.43 g, P = 0.001 and 1.70 ± 0.20 g vs. 2.48 ± 0.19 g, P = 0.001, respectively). Moreover, Group A showed significantly less liver steatosis than Group B. Additionally, Group A led to slightly decreased serum triglyceride (TG) and cholesterol (TC) levels compared to Group B. Western blotting showed that exenatide could prevent HFD-induced upregulation of BMP4 levels and downstream activation of Smad1/5/8 and the P38 MAPK signaling pathway in the liver. Furthermore, exenatide treatment could reduce BMP4 and enhance UCP-1 (an important thermogenin) in brown adipose tissue (BAT). CONCLUSION: Exenatide could improve HFD-induced hepatic steatosis and enhance thermogenesis in BAT, which may be partly attributed to the inhibition of the BMP4-related signaling pathway.